Connected by sea, disconnected by tuna? Challenges to regionalism in the Southwest Indian Ocean. Issue 1 (2nd January 2019) - Andriamahefazafy, M.; Kull, C. A.; Campling, L.
ABSTRACT: Madagascar, Mauritius and Seychelles are at the center of industrial tuna extraction in the Southwest Indian Ocean (SWIO). In this paper, we show that, while a discourse of regionalism between the three islands is prominent, the possibilities of regionalism face deep challenges in relation to the tuna industry. This is due to three factors. First, local perceptions, especially amongst those working in and on the tuna industry, are in disconnection with an 'Indianoceania' vision. Second, the geopolitics between coastal states and distant water fishing nations creates various entanglements including through fishing access revenue and foreign aid. Finally, the materiality of tuna can at times create competition as countries seek to individually maximize benefits from the industry. We argue that the active reinforcement of regional identity and collaboration around this resource is necessary to sustain local benefits into the future.